Consumer preferences for new fermented food products that mix animal and plant protein sources. (June 2021) - Saint-Eve, Anne; Irlinger, Françoise; Pénicaud, Caroline; Souchon, Isabelle; Marette, Stéphan
Highlights: We combined hedonic and willingness to pay (WTP) approaches to study consumer behavior. Information about nutritional and environmental impacts may promote dietary transitions. Participant preference increased as the product's pea percentage decreased. WTP increased with hedonic preferences but was differentially affected by nutritional and environmental information. Developing fermented products that mix animal and plant protein sources is a major challenge. Partially replacing animal ingredients with plant ingredients could enhance dietary sustainability. Abstract: Consumers are being encouraged to increase the proportion of plant protein in their diets to enhance the sustainability of food systems. One approach is to develop plant-protein-rich foods that are acceptable to consumers. This study examined French people's reactions to cheese alternatives—new fermented products that mixed animal and plant protein sources. We conducted experimental sessions with 240 French participants to assess their responses to three fermented products containing different percentages of yellow pea and cow's milk. First, we asked the participants to blind-taste the three products and solicited hedonic scores of products. We then provided the participants with simple information about the products' composition and asked them to taste and score the liking of the products a second time. We also asked consumers to estimate their willingness to pay (WTP) for each product before and after revealing additional information about the nutritional or environmental benefits of consuming pea-based foods. The product with the lowest percentage of pea and the highest percentage of milk received the highest hedonic scores, and WTP was correlated with the hedonic scores. The additional information about the nutritional and environmental benefits of pea-based foods led to significant increases in WTP for two of the fermented products, but not for the least preferred product, namely the one with the highest percentage of pea. This finding suggests that participant reactions to information depended on hedonic preferences.